The Influence Of Profitability, Liquidity, And Firm Size On Firm Value - Murti, Galuh Tresna; Azizah, Charisma Yoan Nurotul (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
This research aimed to determine the impact of profitability, liquidity, and firm size on firm value. The population of the research is 37 primary consumer goods sector issuers listed on the IDX in 2017-2022. By using purposive sampling method and panel data regression test using EViews 12. From this research show that the size of profitability, liquidity, and firm size simultaneously impact firm value. Partially, profitability has an impact on firm value, while liquidity and firm size have no impact on firm value.